Rice Byproduct Compounds: From Green Extraction to Antioxidant Properties - Raffaella Colombo; Giulia Moretto; Marta Barberis; Ilaria Frosi; Adele Papetti (MDPI AG, 2023)
Currently, rice (Oryza sativa L.) production and consumption is increasing worldwide, and many efforts to decrease the substantial impact of its byproducts are needed. In recent years, the interest in utilizing rice kernels, husk, bran, and germ for the recovery of different molecules, from catalysts (to produce biodiesel) to bioactive compounds, has grown. In fact, rice byproducts are rich in secondary metabolites (phenolic compounds, flavonoids, and tocopherols) with different types of bioactivity, mainly antioxidant, antimicrobial, antidiabetic, and anti-inflammatory, which make them useful as functional ingredients. In this review, we focus our attention on the recovery of antioxidant compounds from rice byproducts by using innovative green techniques that can overcome the limitations of traditional extraction processes, such as their environmental and economic impact. In addition, traditional assays and more innovative methodologies to evaluate the antioxidant activity are discussed. Finally, the possible molecular mechanisms of action of the rice byproduct antioxidant compounds (phenolic acids, flavonoids, γ-oryzanol, and vitamin E) are discussed as well. In the future, it is expected that rice byproduct antioxidants will be important food ingredients that reduce the risk of the development of several human disorders involving oxidative stress, such as metabolic diseases, inflammatory disorders, and cancer.